2009
DOI: 10.1039/b905573h
|View full text |Cite
|
Sign up to set email alerts
|

Role of solvation dynamics in the kinetics of solvolysis reactions in microreactors

Abstract: In this contribution we attempt to correlate the dynamical states of water molecules in reverse micelles with a solvolysis reaction in accordance with the activation energy barrier crossing model at the micellar interface. Precise measurement of the different dynamical states of water molecules at the reverse micellar interface with various degrees of hydration is achieved through temperature-dependent solvation dynamics of coumarin 523. The rotational anisotropy studies along with a wobbling-in-cone analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 78 publications
7
28
0
Order By: Relevance
“…water–DX interface). The bound to free type transition of water molecules with temperature is assumed to be governed by an Arrhenius type of activation energy barrier crossing model (46,47). We fit an Arrhenius plot using the <τ s > values listed in Table 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…water–DX interface). The bound to free type transition of water molecules with temperature is assumed to be governed by an Arrhenius type of activation energy barrier crossing model (46,47). We fit an Arrhenius plot using the <τ s > values listed in Table 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such temperature induced transition could be correlated with an Arrhenius type of transition in the following manner. It has been established in earlier studies 31,32,66,67,75,76 that the transition of water molecules at the RM and other microheterogeneous assemblies follows an Arrhenius type barrier crossing model given as:…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…They have shown that water molecules when restricted to the nanometer-scale core of the aggregates behave differently from the bulk as a result of the specific interactions and confined geometries. In this way, recently Verma et al [60] have correlated the dynamical states of water molecules in reverse micelles with the solvolysis reaction of benzoyl chloride in AOT/ isooctane RMs at different W 0 values and temperatures. The observed acceleration of the solvation dynamics with the water content and the temperature increase supports the general view that the mobility of the water molecules in RM increases due to the transition of surface-bound water to free water.…”
Section: Introductionmentioning
confidence: 96%